JOURNAL OF GOVERNMENT & POLITICS : Public Service Integrity Perception : Case Study In Kutai Kartanegara Regency, Indonesia - Dyah Mutiarin (FISIPOL UMY, 2014)
This paper was aimed to measure the integrity of public service at Kutai Kartanegara Regency, East Borneo Province, Indonesia.